An unusual response with long term survival using erlotinib in NSCLC lung with brain metastases. (4th January 2016) - Rastogi, Madhup; Nanda, Sambit Swarup; Prakash, Chandra; Kulshreshtha, Dinkar
Abstract : We present a case of a middle-aged woman with adenocarcinoma of the lung and metastatic brain lesions. In view of her poor general condition and poor compliance to first-line chemotherapy, the patient was kept on tablet erlotinib after whole brain radiotherapy. This novel treatment resulted in a dramatic response with radiological regression in both the primary lung lesion and metastatic intracranial lesions translating in unexpected and ongoing 24-month survival.